In vitro anti-cancer activity of Epipremnum aureum (Bangladesh Journal of Pharmacology, 2024)
In the present study, in vitro anti-cancer activity of aerial parts of Epipremnum aureum extracts was performed using the MCF-7 breast cancer cell line. Soxhlet method was used with different solvents for extract preparation. The amount of apoptosis in MCF-7 cells was assessed using flow cytometry for each of the extracts. The chloroform and ethanol extracts had a considerable cytotoxic effect with IC50 values of 32.9 and 45.8 μg/mL respectively, while the conventional medication 5-fluorouracil produced an IC50 value of 19.2 μg/mL. The microscopic examination of the chloroform and ethanol extracts of E. aureum revealed the presence of apoptotic bodies, nuclear fragmentation, and tiny nuclei with strong chromatin condensation. These results suggest that chloroform extract of E. aureum is more effective against breast cancer.